Analisis Dampak Manajemen Operasi Terhadap Kinerja Perusahaan - Reza Muhammad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Operations management is a series of activities related to planning, organizing, controlling and supervising all resources used in the process of producing goods or services. The main function of operations management is to create quality products or services, at efficient costs, at the right time, and in accordance with market demand. This research is quantitative research that works with numbers and the data is in the form of numbers which are then analyzed using statistics to test hypotheses or to answer specific research questions and to make predictions. This research approach is explanatory research where data collection is carried out simultaneously in one stage (one shot study or in a cross-section through a questionnaire. One of the main impacts of operations management what is good is increasing the efficiency of the production process by designing and managing efficient production processes, companies can optimize the use of available resources, reduce waste, and increase output without increasing significant costs. Effective operations management has a significant impact on various aspects of company performance, including operational efficiency, cost control, product quality and service, and customer satisfaction. By implementing good operations management principles, companies can increase their competitiveness, reduce waste, and improve the customer experience.